2013
DOI: 10.1093/toxsci/kft191
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide RNAi High-Throughput Screen Identifies Proteins Necessary for the AHR-Dependent Induction of CYP1A1 by 2,3,7,8-Tetrachlorodibenzo-p-dioxin

Abstract: The aryl hydrocarbon receptor (AHR) has a plethora of physiological roles, and upon dysregulation, carcinogenesis can occur. One target gene of AHR encodes the xenobiotic and drug-metabolizing enzyme CYP1A1, which is inducible by the environmental contaminant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) via the AHR. An siRNA library targeted against over 5600 gene candidates in the druggable genome was used to transfect mouse Hepa-1 cells, which were then treated with TCDD, and subsequently assayed for CYP1A1-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Interestingly, cholesterol content is also decreased in iL -Sin3a/b mice. This can reflect GCK- or/and FOXO1-independent functions of SIN3A in liver metabolism, for example through its role to regulate mitochondrial activity (Barnes et al, 2014; Pile et al, 2003), or cholesterol biosynthesis (Solaimani et al, 2013). There are likely to be additional functions to hepatic SIN3A, in particular in the development of bile ducts, that account for the abnormal liver function tests, histopathologic abnormalities, and splenomegaly (likely secondary to portal hypertension) seen in mice with constitutive liver deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cholesterol content is also decreased in iL -Sin3a/b mice. This can reflect GCK- or/and FOXO1-independent functions of SIN3A in liver metabolism, for example through its role to regulate mitochondrial activity (Barnes et al, 2014; Pile et al, 2003), or cholesterol biosynthesis (Solaimani et al, 2013). There are likely to be additional functions to hepatic SIN3A, in particular in the development of bile ducts, that account for the abnormal liver function tests, histopathologic abnormalities, and splenomegaly (likely secondary to portal hypertension) seen in mice with constitutive liver deletion.…”
Section: Discussionmentioning
confidence: 99%
“…However, these siRNAs did not significantly reduce induction of CYP1A1 EROD activity (19). It is possible that these subunits are not essential for CYP1A1 induction.…”
Section: Discussionmentioning
confidence: 81%
“…Understanding the regulation of CYP1A1 will therefore contribute not only to an understanding of the dysregulation of AHR target genes but also the resulting toxicity of this dysregulation. We previously reported results from an RNAi high throughput screening we performed that indicated that SIN3A is necessary for TCDD induction of CYP1A1 in murine Hepa-1 cells (19). In this paper, we also demonstrate that overexpression of human SIN3A in Hepa-1 cells transfected with siRNA to mouse SIN3A was sufficient to rescue CYP1A1-mediated EROD activity, which validates our previous results and provides convincing evidence that our observations are a result of effects of the siRNA on SIN3A and not due to off-target effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations